ANALYSIS OF USER SATISFACTION OF THE STUNTING APPLICATION BASED ON ARDUINO UNO USING WEBQUAL 4.0 - Sri Restu Ningsih; Muhammad Amrin Lubis; Cyntia Lasmi Andesti; Muhammad Rizky Hidayat; Alif Budiman Wahabbi (JOISIE (Journal Of Information Systems And Informatics Engineering), 2025)
The high prevalence of stunting that currently occurs is a serious problem faced. This is because stunting checks are still done manually. For this reason, an application for detecting stunting in toddlers using Arduino Uno was designed, in the form of the SIPASBU application (Information System for Preventing Stunting in Mothers and Toddlers) quickly, accurately, and able to provide early treatment using Arduino Uno tools. The problem that occurs is that there are still complaints from health workers when using the SIPASBU application. The purpose of this study is to analyze the satisfaction of SIPASBU application users, in this case health workers at the Puskesmas. Webqual 4.0 is used as a method to evaluate and analyze the SIPASBU application which is used as a medium for online stunting detection. In order for the evaluation to be carried out, assessment variables are needed that refer to three variables, namely Usability, Information, and Service Interaction. The results showed that the Usability value in measuring the quality level of the SIPASBU application was 3.32 with the Good category. The Information Quality value in measuring the quality level of the SIPASBU application is 3.22 with the Good category, for the Interaction Quality value in measuring the quality level of the SIPASBU application is 3.33 with the Good category. The overall value for the WebQual 4.0 indicator obtained is 3.29 in the Good category, so users assess that the SIPASBU application is qualified as a medium for detecting stunting of toddlers at the Puskesmas